The effect of depression on antiretroviral drug non-adherence among women living with HIV in Gondar health facilities, northwest Ethiopia: a prospective cohort study - Zeleke, Tadele Amare; Ayele, Tadesse Awoke; Denu, Zewditu Abdissa; Mwanri, Lillian; Azale, Telake (Frontiers in Psychiatry, 2025)
BackgroundGlobally, depression has been recognized as one of the risk factors for poorer outcomes in human immunodeficiency virus (HIV)- affected populations including women living with HIV (WLWHIV). Additionally, depression continues to be a barrier to antiretroviral therapy (ART) adherence. In African countries, including Ethiopia, depression often goes undetected and untreated for extended periods, leading to prolonged health outcomes. Factors such as the lack of awareness about depression and its impact on ART adherence contribute to its poor management. Understanding depression’s role in ART is crucial for generating evidence to improve individuals’ functionality and treatment outcomes. This study aimed to examine the effects of depression on ART non-adherence among WLWHIV in Ethiopia.MethodsA prospective cohort study was conducted with data collected from 627 study participants who were on stable ART regimens at baseline, 3 months, and 6 months. Depression, the primary exposure variable, was measured using the Patient Health Questionnaire (PHQ-9). Antiretroviral adherence, the dependent variable, was assessed using the Simplified Medication Adherence Questionnaire (SMAQ). Generalized estimating equations (GEEs) were used to examine the association between HIV- related stigma, social support, depression, and ART non-adherence.ResultsThe response rates of the study participants in the 2nd and 3rd phases were 99.7% and 94.4%, respectively, with a mean age of 42.27 years (SD ± 10.51). Depressed WLWHIV had a 2.19 times higher incidence of ART non-adherence compared to non-depressed WLWHIV. In panel data analysis, depression, poor social support, and HIV- related stigma were positively associated with ART non-adherence, with adjusted odds ratios of 1.97 [95% confidence interval (CI) (1.35, 2.87)], 2.15 [95% CI (1.05, 4.38)], and 1.56, [95% CI (1.09, 2.25)] respectively.ConclusionDepression, poor social support, and HIV- related stigma in women living with HIV were associated with ART non-adherence. Addressing these modifiable barriers could significantly enhance ART adherence in these populations.